Mental Health Prevention Activities in Prisons in Central Java: A Case Study - Arintan Nur Safitri; Megah Andriany; Nur Setiawati Dewi (Alta Dharma Publisher, 2021)
Background: Studies explored about mental health prevention activities in prisons were limited to be found. Objective: This study aims to describe mental health prevention activities in prisons in Central Java. Method: This study is a single exploratory case study consisting of three participants who were selected through purposive sampling. Participants are correctional nurses who are involved in mental health care in prisons with a minimum education of Nursing Diploma. The data was collected through semi-structured in-depth interviews and analyzed using thematic analysis with an inductive approach. This study shows that there are various mental health prevention activities provided in each of three prisons in Central Java. Result: Three themes are discussed: 1) mental health assessment, 2) mental health education, and 3) mental health therapies. Conclusion: Mental health assessment consists of mental health screening to the new inmates and mental health observation. Mental health education is provided by giving education which is integrated to physical education and teaching relaxation and how to rebuke. Mental health therapies provided consists of recreational activities, group activity therapy, spiritual guidance, collaboration in providing medication, and diversion of hallucination. Therefore, correctional nurses need to improve their knowledge and skills in providing of mental health prevention activities in prisons.